Identification of a new VHL exon and complex splicing alterations in familial erythrocytosis or von Hippel-Lindau disease - Lenglet, M; Robriquet, F; Schwarz, K; Camps, C; Couturier, A; Hoogewijs, D; Buffet, A; Knight, SJ; Gad, S; Couvé, S; Chesnel, F; Pacault, M; et al. (American Society of Hematology, 2018)
Chuvash polycythemia is an autosomal recessive form of erythrocytosis associated with a homozygous p.Arg200Trp mutation in the von Hippel-Lindau (VHL) gene. Since this discovery, additional VHL mutations have been identified in patients with congenital erythrocytosis, in a homozygous or compound-heterozygous state. VHL is a major tumor suppressor gene, mutations in which were first described in patients presenting with VHL disease, which is characterized by the development of highly vascularized tumors. Here, we identify a new VHL cryptic exon (termed E1′) deep in intron 1 that is naturally expressed in many tissues. More importantly, we identify mutations in E1′ in 7 families with erythrocytosis (1 homozygous case and 6 compound-heterozygous cases with a mutation in E1′ in addition to a mutation in VHL coding sequences) and in 1 large family with typical VHL disease but without any alteration in the other VHL exons. In this study, we show that the mutations induced a dysregulation of VHL splicing with excessive retention of E1′ and were associated with a downregulation of VHL protein expression. In addition, we demonstrate a pathogenic role for synonymous mutations in VHL exon 2 that altered splicing through E2-skipping in 5 families with erythrocytosis or VHL disease. In all the studied cases, the mutations differentially affected splicing, correlating with phenotype severity. This study demonstrates that cryptic exon retention and exon skipping are new VHL alterations and reveals a novel complex splicing regulation of the VHL gene. These findings open new avenues for diagnosis and research regarding the VHL-related hypoxia-signaling pathway.